Excellent Outcomes and Lack of Prognostic Impact of Cell of Origin for Localized Diffuse Large B-cell Lymphoma in the Rituximab Era - Kumar, Anita (Br J Haematol, 2015)
Therapeutic options for limited-stage diffuse large B cell lymphoma (DLBCL) include short- or full-course R-CHOP (rituximab, cyclophosphamide, doxorubicin, vincristine, prednisolone) +/- radiotherapy. The optimal treatment remains unclear. The prognostic value of cell-of-origin (COO) in early stage DLBCL is unknown. Patients with limited-stage DLBCL (stage I or stage II, non-bulky) treated with R-CHOP +/- involved field radiotherapy (IFRT) from 1999 – 2012 were included. COO by the Hans algorithm was analysed in a subset of patients. Of 261 patients, 30% were stage I (N=82), 37% Stage IE (N=96), <1% stage IXEE (N=1), 18% stage II (N=46) and 14% Stage IIE (N=37). The stage-modified IPI stratified patients into prognostically relevant groups. There was no significant difference in progression-free survival (PFS) or overall survival (OS) for patients in the germinal centre B-cell-like (GCB; n=65) and non-GCB cohorts (n=22). Seventeen patients received R-CHOP x 3-4 cycles (Arm A), 147 received R-CHOP x 3-4 cycles + IFRT (Arm B), 48 received R-CHOP x6 cycles (Arm C), and 50 received R-CHOP x6 cycles +IFRT (Arm D). The outcomes were excellent, with 5-year PFS of 82% and 5-year OS of 93%, and were similar across the 4 treatment groups. In the rituximab era, outcomes for limited-stage DLBCL, regardless of treatment approach, were excellent. Baseline COO was not a significant prognostic factor in patients treated with short-course R-CHOP + IFRT.